Math
Home
> Preview
The flashcards below were created by user
eruiz950
on
FreezingBlue Flashcards
.
Get the free mobile app
Take the Quiz
Learn more
x
^{2 }
- y
^{2}
=
(x+y)(x-y)
(x+y)
^{2}
=
(x+y)(x+y)
x
^{2}
+2xy+y
^{2}
(x-y)
^{2}
=
(x-y)(x-y)
x
^{2}
- 2xy + y
^{2}
S
_{n}
=K
_{n}
+ x
K= Constant
n= difference between successive terms
x= Other constant
Card Set Information
Author:
eruiz950
ID:
21854
Filename:
Math
Updated:
2010-06-03 03:37:31
Tags:
MATH formulas
Folders:
Description:
MATH
Show Answers:
What would you like to do?
Get the free app for
iOS
Get the free app for
Android
Learn more
Home
>
Flashcards
> Print Preview